Analisis Pendapatan, Biaya Dan Titik Impas Usaha Pengepul Barang Bekas Di Kota Tangerang - Eki Feyzar Luthfiansyah; Rina Mailasari; Rizka Yuliana; Utari Wulandari; Aminuddin Aminuddin (Indonesian Journal of Economics Application (IJEA), 2018)
In Indonesia, there is a business activity who conducted recycled goods. They collect it from many sources. The activities of this business have long existed in the main cities, especially in the area of Jabodetabek. This business practice is generally conducted by small entrepreneurs. As a business entity, the profit and loss are essential component in order to find out if the entity makes a profit or not. This article reports the results of research on the break-even point on recycled collector in Tangerang City. The results show, this business entity can generate sustainable enough profit. Another research findings are we get any difficulties in obtain accurate data because the industry did not do adequate financial record. On that situation, the policy recommendation that can be implemented by the industry is recording financial report.